Management and Implementation of Holistic-Integrative Early Childhood Education (PAUD-HI) Through Cross-Sector Collaboration: A Case Study of KB Dharma Bhakti, Dawarblandong - Fitri Hidayah; Tri Lailatulqodar Riswati; Diki Darmawan; Umar Chamdan (Universitas Negeri Surabaya, 2025)
This study examines the implementation of Holistic-Integrative Early Childhood Education (PAUD-HI) management at KB Dharma Bhakti, Dawarblandong District, focusing on collaboration between educational institutions and health services. Using a qualitative descriptive approach, data were collected through observations and semi-structured interviews with teachers, the institution’s head, and parents to identify barriers and supporting factors of PAUD-HI implementation. The findings show that KB Dharma Bhakti demonstrates strong internal management and effective teaching practices supported by qualified educators and Contextual Teaching and Learning (CTL) approaches that enhance children’s engagement and holistic development. However, the institution faces major challenges due to the absence of cooperation with health partners such as community health centers (Puskesmas) and village midwives, resulting in limited routine health monitoring, immunization, and developmental screening. This situation restricts early detection of health and developmental issues affecting children’s learning readiness. The study recommends formal collaboration through Memorandums of Understanding (MoUs) and stronger policy frameworks to ensure integration between education and health sectors, improving PAUD service quality.